DYNAMIC SOIL-STRUCTURE INTERACTION IN A LAYERED MEDIUM - Romanel, Celso, 1952- (The University of Arizona., 1987)
The most popular method in dynamic soil-structure interaction analysis is the finite element method. The versatility in problems involving different materials and complex geometries is its main advantage, yet FEM can not simulate unbounded domains completely. A hybrid method is proposed in this research, which models the near field (structure and surrounding soil) by finite elements and the far field by a continuum approach. The system is excited by monochromatic body waves (P and SV) propagating with oblique incidence and harmonic time dependence. The far field problem is solved using Thomson-Haskell formulation associated with the delta matrix technique. The soil profile does not contain any soft layer and the layers are assumed to be linearly elastic, isotropic, homogeneous and perfectly bonded at the interfaces. Two-dimensional (in-plane) formulation is considered and the analysis is performed on both k- and o-planes through time and spatial Fourier transforms of the field equations and boundary conditions. (Abstract shortened with permission of author.)